PERAN GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KESEJAHTERAAN PSIKOSOSIAL SISWA DI SMP DARUTTAQWA DAHANREJO KEBOMAS GRESIK - Moh. Sulthonul Muhid (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This research aims to explore the role of guidance and counseling teachers in overcoming psychosocial problems caused by bullying and high-achievement competition among teenagers. They are prepared using descriptive qualitative methods by collecting data through observation, questionnaires, interviews, and documentation. The research results confirm that guidance and counseling services are integral to school efforts to help students achieve optimal academic success and psychosocial well-being. The role of Guidance and Counseling teachers is vital in providing psychosocial support to students. They are responsible for helping students face various emotional challenges and building the social skills needed in everyday life. Internal and external factors influence students' psychosocial well-being. Schools and parents need to work together to create a supportive environment and help students develop practical coping skills to deal with the stress and problems they face.